Superimposed Mosaicism in Tuberous Sclerosis Complex Presenting as Predominantly Right-Sided Facial Angiofibromas - Jane Hoban; Marion Leahy; Logeswaran Selvarajah; Muriel Sadlier; Laoise Griffin (Clinical and Experimental Dermatology, 2026)
A 9-year-old boy presented with flesh-coloured papules present since early childhood and were gradually increased in size and number. Clinical examination revealed multiple small, firm papules arranged in a linear configuration, more conspicuous on the right side compared with the left. Given the asymmetric distribution of the lesions, mosaic TSC was suspected. Molecular analysis of DNA extracted from affected skin identified two pathogenic somatic variants involving TSC1. Asymmetrical brain MRI findings supported a diagnosis of superimposed mosaic TCS. Superimposed TSC may present with minimal systemic involvement and subtle radiological findings, contributing to potential under-recognition. Accurate classification has implications for prognosis, surveillance and genetic counselling.